Main Profile

At A Glance

Transformations of Graphs : Reflections y=-f(x), y=f(-x) Proof : ExamSolutions

In this tutorial I demonstrate why y= - f(x) reflects a graph in the x-axis and why y=f(-x) reflects a graph in the y-axis.To see this and other tutorials go to http://www.examsolutions.co.uk/
Length: 09:02

Contact

Questions about Transformations of Graphs : Reflections y=-f(x), y=f(-x) Proof : ExamSolutions

Want more info about Transformations of Graphs : Reflections y=-f(x), y=f(-x) Proof : ExamSolutions? Get free advice from education experts and Noodle community members.

  • Answer

Ask a New Question